A Conceptual Study On Hemanta Ritucharya - Bhagat, Seema; Ramamurthy, Aku; Rathore, Poonam (International Research Journal of Ayurveda & Yoga, 2021)
Purushoayam loksamitam, an individual is an epitome of the universe as all the material and spiritual phenomena of the universe are present in the individual and all those present in the individual are also contained in the universe [1]. It means whenever there is any alteration in surrounding environment it affects humans’ body as well. In order to cope with all those changes in the surrounding environment, Ayurvedic Acharyas have mentioned Dincharya (day time regimen), Ratricharya (night regimen), Ritucharya (seasonal regimen). In Ayurvedic literature, year is divided into six Ritus (seasons) according to the movement of the sun. Three Ritus Shishira, Vasanta, Grishma comes under Uttarayana or Aadankala and the other three ritus Varsha, Sharada and Hemanta comes under Dakshinayana or Visarga kala. In Hemanta Ritu Moon is more powerful than the Sun which increases human beings Bala (strength) and Agni (digestive fire) step by step. So, Snigdha (unctuous), Amla (sour), Madhura (sweet) and Lavana (salty) dietary substances should be taken in Hemanta Ritu. In this study, the characteristics, dietetics, regimen along with the procedures which should be followed in Hemanta Ritu are thoroughly reviewed.